Asymptomatic Malaria Infection Affects the Interpretation of Biomarkers of Iron and Vitamin A Status, Even after Adjusting for Systemic Inflammation, but Does Not Affect Plasma Zinc Concentrations among Young Children in Burkina Faso. Issue 12 (1st October 2014) - Wessells, K Ryan; Hess, Sonja Y; Ouédraogo, Zinewendé P; Rouamba, Noel; Ouédraogo, Jean-Bosco; Brown, Kenneth H
Abstract: Background: Biomarkers of iron [plasma ferritin (pF)], vitamin A [retinol binding protein (RBP)], and zinc status [plasma zinc (pZn)] are affected by the acute phase response, independent of micronutrient status. Objective: The objective of these analyses was to assess how asymptomatic malaria infection affects the interpretation of these biomarkers after adjustment for elevated acute phase proteins (APPs). Methods: Soluble transferrin receptor (sTfR), pF, RBP, and pZn concentrations were measured among 451 asymptomatic children aged 6–23 mo in Burkina Faso and adjusted for elevated APP (C-reactive protein ≥5 mg/L and/or α-1-acid-glycoprotein ≥1 g/L) based on a 4-group categorical model. Plasma histidine-rich protein II (HRP2) concentrations ≥0.75 μg/L were considered indicative of current or recent malaria parasitemia. Results: Of the children in the study, 57.4% had at least 1 elevated APP, and 48.5% had elevated HRP2. After adjusting for APP, children with elevated HRP2 had higher pF (23.5 ± 1.5 μg/L vs. 11.1 ± 0.8 μg/L; P < 0.001) and lower RBP (0.79 ± 0.01 μmol/L vs. 0.92 ± 0.01 μmol/L; P < 0.001) than those without, but there were no differences in pZn among those with and without elevated HRP2 (64.9 ± 12.7 μg/dL vs. 64.9 ± 11.1 μg/dL; P = 0.98). Children with elevated HRP2 had higher sTfR than those without (17.6 ± 0.5 mg/L vs. 12.3 ± 0.4 mg/L; P < 0.0001). After adjusting for HRP2, along with APP, the estimated prevalence of iron deficiency (pF < 12 μg/L) increased from 38.7% to 50.6% and vitamin A deficiency (RBP < 0.84 μmol/L) decreased from 33.4% to 27.7%. Conclusions: Asymptomatic malaria is associated with indicators of micronutrient status, even after adjusting for APP. Adjusting indicators of iron and vitamin A status based only on APP may inaccurately estimate the prevalence of micronutrient deficiencies in settings with a high prevalence of malaria and inflammation. This trial was registered at clinicaltrials.gov as NCT00944853.